قضايا تعليم المرأة : دراسة مقارنة بين الحديث الشريف وكتاب الحوار لكونفوشيوس - رو، ما (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research aims to study the issues of women's education in the Hadith and The Analects, and to show similarities and differences in the education of women between them through comparison and interview. The study followed the method of inductive and analytical approach and comparative method, through which the study explained the education of women in the Hadith and The Analects. The study presented a definition of The Analects and Confucianism by explaining the principles and advantages of women's education and the relationship between teacher and learner in the Hadith and The Analects. The study also analyzed the similarities and differences in women's education in these two books. The main findings of the study are as follows: First, education and the education of women have an important place in Islam and the ideas of Confucius which determine the evolution of the nation and its decline. Second, scientists and teachers are important and indispensable factors in Islam and Confucius' ideas on women and education. Third, the relationship between the teacher and the learner in the Hadith and The Analects is a relationship of harmony, equality and mutual assistance, and these interdependent relations are a model that must be sustained. Fourthly, the education of women in the Hadith and The Analects has similarities with respect to educational principles, and also has differences in educational purposes, educational content, and educational sites. Fifth, women and men have equal rights and Islam never ignores the education and status of women. The researcher intends to remove misunderstanding about Islam in the minds of non-Muslims through this study in order to guide them to the true religion of Allah. For the contemporary situation, exchanges and understanding between these two cultures can help remove pre-conceived notions on Islam and Confucianism